Upaya Penurunan Emisi GRK Melalui ”Green Building” - Akhya Ansori; Dian Wahyudin (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2020)
Climate change is a problem that requires integrated action at various levels of government and also in the fields of politics, economics and society. National, regional and local governments have different and complementary roles in developing mitigation strategies and climate adaptation. This research aims to provide an overview of how Green Building is one of the mitigation strategies to reduce GHG emissions. The method used in this study is qualitative research, to analyze the scientific literature that has been produced regarding green building mitigation strategies. The results showed that the Green Building mitigation strategy gave a significant contribution in reducing GHG emissions. There were only a few factors that were still a barrier to reducing GHG emissions through Green Building, namely law enforcement and many buildings that already existed had not applied the Green Building concept issued by government.. In addition, the handling of climate change cannot be carried out by stakeholders only but must involve community and private participation.